USAHA-USAHA PEMASARAN DALAM MENGHADAPI PERSAINGAN BISNIS INDUSTRI JASA OLAH RAGA (Kasus Industri Olah Raga Futsal Lancang Kuning Di Kecamatan Tampan Pekanbaru) - ", Khairunnas; Herianto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Futsal has become the current trend in young people in big cities in Indonesia, a lot of young people to change the habits of life of silence in the House with a number of electronic games such as playstation (PS), computer (PC) and so becomes a nuanced game health. Many reasons why futsal popular, other than to maintain fitness, futsal has also coached managing emotions and improve teamwork. The purpose of this research is to find out which marketing efforts are doing the Sport Centre Langcang Yellow Futsal in the face of competition in the Subdistrict of Pekanbaru, HandsomeTheoretically, futsal coaching someone to hurry in taking decisions, rules of the game to mention that each execution (kick or roll) must be done within a span of four minutes, over the span of time rewarded violations. Futsal is also forming a player to always focus on accepting and feed and scored it really should be done quickly and mature. To train co-operation between the player and the cohesiveness of the team futsal players, for some, is not just a sport but a lifestyle has become an interesting and dynamic.From the results of the overall analysis of the Business – marketing efforts undertaken by Sassy Yellow is good enough, it can be seen from the responses of the respondents against the product marketing efforts deliver assessment quite well.Keywords: product, Price, promotion, location, and service